Bid-Ask Price Competition with Asymmetric Information between Market-Makers - CALCAGNO, RICCARDO; LOVO, STEFANO (Review of Economic Studies, 2006)
This paper studies the effect of asymmetric information on the price formation process in a quote-driven market. One market-maker receives private information on the value of the quoted asset and repeatedly competes with market-makers who are uninformed. We show that despite the fact that the informed market-maker's quotes are public, the market is never strong-form efficient with certainty until the last stage. We characterize a reputational equilibrium in which the informed market-maker influences and possibly misleads the uninformed market-makers' beliefs. At this equilibrium, a price leadership effect arises, the informed market-maker's expected pay-off is positive and the rate of price discovery increases in the last stages of trade.